2015
DOI: 10.3823/1676
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with survival of burned patients

Abstract: Background: It is scarce in the literature studies regarding treatment and objective analysis of the survival chances of burned patients. Some investigations indicates the need for obtaining specific data to the population studied and characteristics such as social condition and nutritional status are suggested to be relevant to the patient's evolution. We aimed to describe the mortality of a Treatment Center Burn Unit (BU) in Brazil. Methods:We analyzed 76 burned victims hospitalized with a fatal outcome in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…This indicates that the younger the patients the higher the survival rates. This is also supported by a study conducted by Zanasi et al, (2015). Their study reported that the elderly group had a smaller survival rate with a higher risk of death.…”
Section: Discussionsupporting
confidence: 63%
“…This indicates that the younger the patients the higher the survival rates. This is also supported by a study conducted by Zanasi et al, (2015). Their study reported that the elderly group had a smaller survival rate with a higher risk of death.…”
Section: Discussionsupporting
confidence: 63%